Diagnostic accuracy of serum proteinase 3 antineutrophil cytoplasmic antibodies in children with ulcerative colitis. Issue 6 (29th October 2020) - Mizuochi, Tatsuki; Arai, Katsuhiro; Kudo, Takahiro; Nambu, Ryusuke; Tajiri, Hitoshi; Aomatsu, Tomoki; Abe, Naoki; Kakiuchi, Toshihiko; Hashimoto, Kunio; Sogo, Tsuyoshi; Takahashi, Michiko; Etani, Yuri; et al.
Abstract: Background and Aim: Serologic markers such as myeloperoxidase (MPO) antineutrophil cytoplasmic antibodies (ANCA) (MPO‐ANCA) have been used to screen patients for ulcerative colitis (UC). However, MPO‐ANCA shows limited accuracy in Asians. Proteinase 3 ANCA (PR3‐ANCA) has performed better at UC diagnosis in Japanese adults than MPO‐ANCA. The present study aimed to evaluate usefulness of PR3‐ANCA for diagnosis of UC in Japanese pediatric practice. Methods: Patients under 17 years old undergoing assessment at 12 Japanese pediatric centers between November 2016 and February 2018 were prospectively enrolled and divided into groups with UC, Crohn's disease (CD), intestinal disease control (IC), and healthy control (HC). Serum PR3‐ANCA and MPO‐ANCA were analyzed using chemiluminescence enzyme immunoassay kits. Results: Sera from 367 patients (148 with UC at a median age of 12 years; 120 with CD, 13 years; 56 with IC, 10.5 years; and 43 with HC, 10 years) were examined. Median PR3‐ANCA values in UC (1.6 U/mL) were greater than in CD (0.2; P < 0.001), IC (0.15; P < 0.001), and HC (0.1; P < 0.001). In receiver operating characteristic curve analyses, the area under the curve for PR3‐ANCA was 0.79, significantly greater than for MPO‐ANCA (0.58; P < 0.001). Using a cut‐off value of 0.8 U/mL determined from the receiver operating characteristic analyses, PR3‐ANCA showed significantly greater sensitivity (64.9%) than MPO‐ANCA (cut‐off, 0.2 U/mL; sensitivity, 19.6%; P < 0.001) and good specificity (83.6%). Conclusions: In Japanese children and adolescents, PR3‐ANCA performed better as a serologic marker for diagnosis of UC than MPO‐ANCA. To our knowledge, this is the first report of such a comparison.